Coastal water bacteriophages infect various sets of Vibrio parahaemolyticus sequence types - Brossard Stoos, Kari A.; Ren, Jennifer; Shields-Cutler, Robin R.; Sams, Kelly L.; Caldwell, Shannon; Ho, Marvin B.; Rivara, Gregg; Whistler, Cheryl A.; Jones, Stephen H.; Wiedmann, Martin; DeMent, Jamie; Getchell, Rodman G.; et al. (Frontiers in Microbiology, 2022)
Gastrointestinal illnesses associated with the consumption of shellfish contaminated with Vibrio parahaemolyticus have a negative impact on the shellfish industry due to recalls and loss of consumer confidence in products. This bacterial pathogen is very diverse and specific sequence types (STs), ST631 and ST36, have emerged as prevalent causes of Vibrio foodborne disease outbreaks in the US, though other STs have been implicated in sporadic cases. We investigated whether bacteriophages could be used as a proxy to monitor for the presence of distinct V. parahaemolyticus STs in coastal waters. For this purpose, bacteriophages infecting V. parahaemolyticus were isolated from water samples collected on the Northeast Atlantic coast. The isolated phages were tested against a collection of 29 V. parahaemolyticus isolates representing 18 STs, including six clonal complexes (CC). Four distinct phages were identified based on their ability to infect different sets of V. parahaemolyticus isolates. Overall, the 29 bacterial isolates segregated into one of eight patterns of susceptibility, ranging from resistance to all four phages to susceptibility to any number of phages. STs represented by more than one bacterial isolate segregated within the same pattern of susceptibility except for one V. parahaemolyticus ST. Other patterns of susceptibility included exclusively clinical isolates represented by distinct STs. Overall, this study suggests that phages populating coastal waters could be exploited to monitor for the presence of V. parahaemolyticus STs known to cause foodborne outbreaks.